From Hand Drawings to Computer Visuals: Confronting Situated and Institutionalized Practices in an Architecture Firm - Groleau, Carole; Demers, Christiane; Lalancette, Mireille; Barros, Marcos (Organization Science, 2012)
In recent years, there has been an increasing interest in practice-based studies of organizational change. Most of this research does not explicitly consider the tension between situated and sociohistorical practices that are central to the transformation of work practices associated with an episode of change. In our study of the impact of off-the-shelf three-dimensional rendering software on the daily practice of architects in a small, highly regarded firm, we explore the incompatibility between these different levels of practice. By building on the concept of contradiction drawn from activity theory, we identify patterns of challenges, reenactments, and enactments through which situated change simultaneously reproduces and questions institutionalized practices.